Primary rhabdomyosarcoma of the breast in a 17-year-old girl: Case report. Issue 49 (December 2017) - Kim, Do Young; Seol, Young Mi; Kim, Hyojeong; Kim, Ahrong; Choi, Young Jin
Abstract: Rationale: Primary rhabdomyosarcoma of the breast is very rare disease with poor prognosis and no definitive treatment has yet been established. Patient concerns: A 17-year-old girl presented with right breast mass without distant metastasis in image study. Diagnosis: The result of core needle biopsy was intraductal carcinoma; however, histopathologic finding after mastectomy was primary rhabdomyosarcoma of breast. Interventions: Adjuvant chemotherapy was recommended because resection margin was involved by tumor cells, but she did not visit the clinic anymore. Five months later, tumor recurred with local invasion and chemotherapy of vincristine, doxorubicin, and cyclophosphamide alternating with ifosfamide and etoposide (VAC/IE) was done. Outcomes: In the course of chemotherapy and sequential follow-up, there was no tumor growth until now. Lessons: Primary breast rhabdomyosarcoma is an uncommon disease, as a result diagnosis is often delayed. For the same reason, there is little information about treatment. This report may be helpful for managing the disease.